Oxidation of simulated wastewater by Fe2+-catalyzed system: The selective reactivity of chlorine radicals and the oxidation pathway of aromatic amines. (March 2023) - Lai, Xiaojun; Huang, Nuoyi; Zhao, Xiaohua; Li, Yang; He, Yao; Li, Jiesen; Deng, Jinhuan; Ning, Xun-an
Abstract: Aromatic amines (AAs), a characteristic pollutant with electron-donating groups in textile industry, having high reactivity with reactive chlorine free radicals, is probably the precursor of chlorinated aromatic products in advanced oxidation treatment. In this study, Fe2+/peroxydisulfate (PDS)/Cl- and Fe2+/H2O2/Cl-systems were used to treat four kinds of AAs (5-Nitro-o-toluidine (NT), 4-Aminoazobenzol (AAB), O-Aminoazotoluene (OAAT), 4, 4′-Methylene-bis(2-chloroaniline) (MBCA)) in simulated wastewater, and the selectivity of various reactive species to AAs, the oxidation law and pathway of AAs were explored. The results showed that dichloride anion radical (Cl2·-) could effectively oxidize four AAs, and chlorine radical (·Cl) was strongly reactive to AAB and MBCA, especially MBCA. The largest f – (Fukui function) of MBCA is 0.0822, which is the lowest of the four AAs, so ·Cl might be more sensitive to electrophilic point than hydroxyl radical (·OH). The oxidation pathway of NT and MBCA showed that ·Cl mainly played the role of electron transfer to AAs instead of generating chlorinated products, but the addition of ·OH to –NH2 generated aromatic nitro compounds with higher toxicity than NT and MBCA. Therefore, the electron transfer of ·Cl and Cl2·- could not only improve the removal of AAs but also reduce the generation of toxic products. This study found that the reactivity of reactive chlorine free radicals was not necessarily related to chlorination, which provided a theoretical basis for the further studies into the formation mechanism of chlorination products. Graphical abstract: Image 1 Highlights: The oxidation of MBCA was obvious in the presence of a large amount of ·Cl. ·Cl may be more sensitive to the low-activity electrophilic point than ·OH. ·Cl or Cl2 ·- has high reactivity with AAs and does not generate chlorinated products. Reducing toxic products in the process of AAs degradation by electron transfer.